Virulence traits and gene profiles of Vibrio alginolyticus from farmed red drum in Vietnam - NGUYEN NAM QUANG; NGUYEN DUC QUYNH ANH; NGUYEN THI HUE LINH; CAROLA VENTURINI; FRANSISCA SAMSING; NGUYEN NGOC PHUOC (Society for Indonesian Biodiversity, 2026)
Abstract. Quang NN, Anh NDQ, Linh NTH, Venturini C, Samsing F, Phuoc NN. 2026. Virulence traits and gene profiles of Vibrio alginolyticus from farmed red drum in Vietnam. Biodiversitas 27 (1): d270145. https://doi.org/10.13057/biodiv/d270145. Vibrio alginolyticus is an emerging bacterial pathogen associated with hemorrhagic disease and mortality in red drum (Sciaenops ocellatus) and other marine fish species. This study investigated virulence phenotypes and virulence-associated gene profiles of V. alginolyticus isolates infecting red drum, which is strain-dependent and reflects the combined expression of multiple phenotypic traits rather than the presence of individual virulence genes alone. Twenty V. alginolyticus isolates obtained from diseased red drum farmed in Hue City, central Vietnam, were evaluated for swimming motility, extracellular enzyme activity, and biofilm formation, and a composite virulence score was calculated using min-max normalized phenotypic data. Based on these scores, ten high-ranking isolates were selected for PCR screening of sixteen virulence-associated genes. Marked phenotypic variability was observed among isolates, with motility and extracellular enzyme activity contributing most strongly to virulence differentiation, whereas biofilm formation was generally weak to moderate. Fifteen genes were detected, including flagellar and motility-related genes (flaA, flaC, flgE, flrA, flrB, flrC, and flaK), hemolysin-related genes (trh and tlh), an adhesion gene (tcpA), secretion system components (vopB, vopD, and vgrG), and iron-acquisition genes (pvuA and pvsA), whereas tdh was not detected. Among the isolates, VA15 and VA17 exhibited the highest motility and extracellular enzyme activities, while most isolates formed weak but detectable biofilms. Pathogenicity testing confirmed that isolate VA15, identified as the most virulent based on in vitro profiling, caused dose-dependent mortality in red drum, with an LD50 of 4.0 × 104 CFU/fish (95% CI: 3.2 × 104-5.1 × 104 CFU/fish). Overall, this study provides baseline phenotypic and molecular data on V. alginolyticus infecting farmed red drum in central Vietnam and contributes to understanding virulence variability among isolates in marine cage aquaculture systems.